Reações fotoquímicas promovidas por luz visível para a síntese de compostos heterocíclicos - Caiuby, Clarice Alves Dale (Universidade Federal de São Carlos, 2017)
In the last decades, the emphasis and application of the principles of Green Chemistry have inspired a change of behavior, both in industry and academy, towards a more sustainable chemistry aiming the synthesis of the desired product with a lower number of steps, high yields and the use of nontoxic hazardous chemicals. In this context, the increasing recognition of the environmental benefits originated from the visible-light-induced photochemical reactions, when compared to the thermal conventional methods, is motivating the scientific community to develop new photochemical approaches that are more efficient and simpler to operate, focusing on the development of new strategies for the synthesis of biologically active organic compounds. Efficient synthetic approaches for the formation of heterocycles based on indolines, 2,3-dihydrobenzofurans and 6-(trifluoromethyl)phenanthridine were developed through radical cascade reactions promoted by visible light. In addition to synthetic development, the mechanisms of the reactions were also investigated by a set of controlled experiments, spectroscopic studies and characterization techniques.
Photochemical reactions promoted by visible light for the synthesis of heterocyclic compounds
Keywords: Síntese Orgânica; Fotoquímica; Heterociclos; Complexos Doador-Aceptor de Elétrons; Tris(trimetilsilil)silano; Compostos organofluorados; Reações Radicalares em Cascata; CIENCIAS EXATAS E DA TERRA::QUIMICA